Antagonism of GABA-B but not GABA-A receptors in the VTA prevents stress- and intra-VTA CRF-induced reinstatement of extinguished cocaine seeking in rats. (March 2016) - Blacktop, Jordan M.; Vranjkovic, Oliver; Mayer, Matthieu; Van Hoof, Matthew; Baker, David A.; Mantsch, John R.
Abstract: Stress-induced reinstatement of cocaine seeking requires corticotropin releasing factor (CRF) actions in the ventral tegmental area (VTA). However the mechanisms through which CRF regulates VTA function to promote cocaine use are not fully understood. Here we examined the role of GABAergic neurotransmission in the VTA mediated by GABA-A or GABA-B receptors in the reinstatement of extinguished cocaine seeking by a stressor, uncontrollable intermittent footshock, or bilateral intra-VTA administration of CRF. Rats underwent repeated daily cocaine self-administration (1.0 mg/kg/ing; 14 × 6 h/day) and extinction and were tested for reinstatement in response to footshock (0.5 mA, 0.5" duration, average every 40 s; range 10–70 s) or intra-VTA CRF delivery (500 ng/side) following intra-VTA pretreatment with the GABA-A antagonist, bicuculline, the GABA-B antagonist, 2-hydroxysaclofen or vehicle. Intra-VTA bicuculline (1, 10 or 20 ng/side) failed to block footshock- or CRF-induced cocaine seeking at either dose tested. By contrast, 2-hydroxysaclofen (0.2 or 2 μg/side) prevented reinstatement by both footshock and intra-VTA CRF at a concentration that failed to attenuate food-reinforced lever pressing (45 mg sucrose-sweetened pellets; FR4 schedule) in a separate group of rats. These data suggest that GABA-B receptor-dependent CRF actions in the VTA mediate stress-induced cocaine seeking and that GABA-B receptor antagonists may have utility for the management of stress-induced relapse in cocaine addicts. Highlights: VTA GABA-B receptor antagonism using 2-hydroxysaclofen prevented shock and intra-VTA CRF-induced cocaine seeking. Intra-VTA 2-hydroxysaclofen alone had no effect on food-reinforced lever pressing or cocaine seeking. VTA GABA-A receptor antagonism using bicuculline had no effect on shock and intra-VTA CRF-induced cocaine seeking.